Influence of Family Environment on Stunting Prevention among Toddlers in Huristak Public Health Center, Padanglawas Regency - Rosmainun Rosmainun; Rika Apripan; Nayodi Permayasa (Jurnal Ilmiah Kesehatan Masyarakat : Media Komunikasi Komunitas Kesehatan Masyarakat, 2026)
Background: Stunting is a condition of impaired growth and development in toddlers caused by chronic malnutrition over a prolonged period. One of the key factors influencing the occurrence of stunting is the family environment. This includes parenting practices, the level of nutritional knowledge, and the availability and utilization of healthcare facilities. This study aims to analyze the influence of family environmental factors, including parenting practices, maternal nutritional knowledge, household sanitation, clean water availability, and access to healthcare services, on stunting prevention among toddlers in the working area of Huristak Public Health Center, Padanglawas Regency. Method: This research was an observational study with a cross-sectional design. A total of 286 mothers with toddlers were selected using purposive sampling. The study collected primary data through structured questionnaires and anthropometric measurements, including toddler height/length-for-age, maternal characteristics, parenting practices, nutritional knowledge scores, household sanitation conditions, availability of clean water, and utilization of healthcare services. Data were analyzed using chi-square tests and logistic regression. Results: This study finds that the availability of clean water (p = 0.001), household sanitation conditions (p = 0.001), maternal nutrition education (p = 0.001), and access to basic healthcare services (p = 0.001) have a significant influence on stunting prevention among toddlers. The most influential variable is access to basic healthcare services Exp.(B)= 15.695). Conclusion: It is recommended that stunting prevention efforts focus on improving access to basic healthcare services, supported by enhancements in sanitation, clean water availability, and nutrition education.